Reporting Indonesia’s New E-Cigarette/Tobacco Regulation (PP 28/2024): Public-Health vs Industry Frames - Amir, Andi Subhan; Pangkam, Moti; Joohs, Markus; Prastowo, FX Ari Agung (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2026)
Background: Indonesia’s PP 28/2024 reshapes controls on tobacco and e-cigarette products, making news coverage a crucial venue where policy meaning is constructed. Prior research on media framing and health communication indicates competition between public-health frames (risk, youth protection, efficacy) and industry frames (jobs, costs, consumer choice), motivating hypotheses about outlet differences, headline–body congruence, source–frame coupling, and timing shifts. Purpose: To describe the balance of public-health versus industry frames in Indonesian online news on PP 28/2024 and assess headline–body alignment, sourcing patterns, and early temporal trends. Methods: Quantitative content analysis (unit: article) across five major outlets, August 2024–August 2025; codebook for dominant frame, headline frame, tone, source mix, and evidence cues; 15% double-coding planned (target κ ≥ 0.70); χ² with Cramér’s V, McNemar tests, descriptive tables, and a monthly trend line as primary outcomes. Results: A 10-item pilot (five outlets) found industry frames 6/10 (60%) and public-health frames 4/10 (40%); headline–body agreement was 10/10 (100%). Outlet × frame association was χ² = 10.000, p = .075, Cramér’s V = .707. Public-health–framed pieces more often referenced primary law; later coverage tilted toward economic and compliance narratives, consistent with framing theory and efficacy-timing expectations. No adverse events apply. Conclusion: Early coverage shows competitive framing with strong headline integrity but uneven verification of economic claims. Full-sample analysis will test outlet differences and source–frame coupling and inform practice on mirroring legal specifics, balancing sources, and sustaining risk-and-efficacy context. Implications: Newsrooms should strengthen verification by linking rule-based stories to relevant PP 28/2024 provisions, adding minimal context for numerical claims using official data, and diversifying expert sources to support evidence-based public understanding.